Multireligious Culture for the Development of Tolerance Character in Elementary School - Munajah, Munajah; Wantini, Wantini; Widodo, Hendro; Hopid, Abdul; Perawironegoro, Djamaluddin (Journal of Indonesian Progressive Education, 2026)
The study entitled Multireligious Culture for the Development of Tolerance Character was motivated by the idealism of schools as safe spaces that facilitate interfaith interaction. However, reality shows that there is bullying against Catholic students, exclusion of Hindu students, and feelings of marginalization among non-Muslim teachers due to the lack of multireligious interaction. This condition prompted the school to initiate a multireligious culture as a strategy to strengthen tolerance. This study uses a descriptive qualitative approach to describe the implementation of a multireligious culture, the profile of the school community's tolerance character, and its contribution to the development of student tolerance. Data were collected through observation, documentation, and in-depth interviews with informants selected using purposive sampling, including the principal, teachers, and students of Islam, Catholicism, and Hinduism. Data analysis was conducted through reduction, presentation, and conclusion drawing, with validity testing using source and technique triangulation. The results of the study show that: 1) multireligious culture is interpreted as a system of values, beliefs, and social practices based on three layers of culture (basic assumptions, values, and artifacts) that emphasize harmony and non-discrimination; 2) the character of tolerance is reflected through six indicators: recognition of differences, mutual respect, freedom of belief, coexistence, self-control, and justice; 3) the contribution of multireligious culture to the development of the character of tolerance takes place systematically through three layers of culture. First, artifacts in the form of symbols of love and joint activities between religious adherents; second, embraced values, namely mutual respect, harmony, and justice, are instilled through vision & mission, rules and regulations, and role models; third, the underlying assumptions of the school community are that diverse religious beliefs are a natural reality and that human relationships are inclusive, egalitarian, and collaborative.